A low cost one pot synthesis of biodiesel from waste frying oil (WFO) using a novel material, β-potassium dizirconate (β-K2Zr2O5) - Singh V.; Bux F.; Sharma Y.C. (My University, 2025)
Biodiesel was synthesized from waste frying oil (WFO) using β-potassium dizirconate (β-K2Zr2O5) as a novel heterogeneous catalyst. Synthesized catalyst was characterized by X-ray diffractometry (XRD), thermogravimetric analysis (TGA), attenuated total reflectance fourier transform infrared spectroscopy (ATR-FTIR), particle size analyser, scanning electron microscopy (SEM), BET surface area and basicity. Various reaction conditions such as molar ratio of methanol: oil, catalyst amount (wt%), reaction temperature, time and reusability of catalyst were studied for transesterification reaction with the catalyst, β-K2Zr2O5. High biodiesel conversion of 96.85% was observed at a 10:1 M ratio (alcohol: oil), 4 wt% catalyst at 65 °C for 2 h. WFO was characterized by GCMS and biodiesel conversion was ascertained by Fourier transform nuclear magnetic resonance (1H and 13C FTNMR) spectroscopy. It was first time that β-potassium dizirconate was used as a catalyst for biodiesel synthesis. The catalyst was reused up to five times without significant loss in its activity. Physical and chemical properties of FAME such as flash point, fire point, cloud point, density, and kinematic viscosity were deliberated. © 2016 Elsevier Ltd.